Abuso do direito de minoria em matéria societária - Gasperini, Luiza Rossi Carneiro (2023)
This study analyzes the cases of abuse of voting rights committed by minority shareholders in the context of joint stock companies. A review of the principles, institutions and concepts of the matter is carried out in order to touch on the main points for the understanding of the theme "Minority Abuse". This is the study of the abuse of the impediment of the majority, originating from the impediment of the majority to cast their votes. In addition, it is also about the abuse of the exercise of the veto right, conferred to the minority, with jurisprudential analysis and case studies. Finally, we analyze the phenomenon of abuse of the exercise of the right of election and representation in the main corporate bodies of the joint stock company